2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34289
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-engineer Career Bias and Its Relationship to Engineering Design Self-efficacy among Biomedical Engineering Undergraduates

Abstract: Biology and Chemistry from St. Francis College in Ft. Wayne, Indiana and his Ph.D. in Physiology from the University of Arizona. Will did his postdoctoral training in Molecular Biophysics at the University of Vermont. His research interests include novel assessments of educational efficacy, the molecular basis of cell movement, and the mitigation of infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…While it is important to consider how educators can better support BME students interested in pursuing industry positions given these concerns, recent exploratory work indicates that many BME students may instead or also be considering non-engineering or nonindustry career pathways upon graduation (e.g., K-12 education, government, non-profit, etc.). 7,8,26,29 Some general research on engineering career pathways showed that students who complete an engineering degree program do not always pursue engineering careers. One such study that collected data from engineering majors at two institutions found that completing an engineering degree was not always linked to a commitment to perform engineering work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is important to consider how educators can better support BME students interested in pursuing industry positions given these concerns, recent exploratory work indicates that many BME students may instead or also be considering non-engineering or nonindustry career pathways upon graduation (e.g., K-12 education, government, non-profit, etc.). 7,8,26,29 Some general research on engineering career pathways showed that students who complete an engineering degree program do not always pursue engineering careers. One such study that collected data from engineering majors at two institutions found that completing an engineering degree was not always linked to a commitment to perform engineering work.…”
Section: Introductionmentioning
confidence: 99%
“…7 They interpreted these patterns as an indicator that BME graduates may view their degrees as bridges to other positions (e.g., medical school or other professional programs). Some other exploratory research indicates that students may pursue BME as a means to combine engineering with other career interests (e.g., clinical careers 8 or careers that serve or help others 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…While research suggests that not all BME graduates wish to enter industry careers, other motivations students have for pursuing a BME undergraduate degree are relatively understudied in the current literature. Some preliminary research indicates that BME may be attractive to students as a way to combine engineering with their other career interests (e.g., clinical careers [16] or a career that allow them to help others [17]).…”
Section: Introductionmentioning
confidence: 99%
“…This implies an equivalent self-concept among BME majors as clinicians and as engineers. Indeed, this has been shown to be the case in previous work [2]. These data sets were small, however, and they left unknown how malleable self-concept may be over the course of a single semester, for different groups, or in different learning environments.We performed a multi-year study of BME students' career self-concept as engineers and as clinicians.…”
mentioning
confidence: 95%
“…This is sometimes referred to as the "stereotype-incongruent pairing." Reprinted from our previous work [2]. 2.…”
mentioning
confidence: 99%